Critical thinking of elementary school students in solving numeracy problems in terms of learning styles: - Dwi Alfan Ashari; Via Yustitia; Susilo Hadi; Tommy Tanu Wijaya (UNION : Jurnal Ilmiah Pendidikan Matematika, 2025)
This study aims to describe students’ critical thinking abilities in solving numeracy problems in terms of four learning styles: activist, theorist, pragmatist, and reflector. A qualitative descriptive approach was employed, involving students who represent each learning style as classified by the Honey and Mumford model. Data were collected through numeracy tests and in-depth interviews to explore students' reasoning processes and critical thinking indicators. The findings indicate that students with an activist learning style tend to excel in the reasoning indicator, as they are able to explain their problem-solving strategies clearly and appropriately. However, their solutions often lack thoroughness, with some steps being overlooked. Students with a theorist learning style show strengths in the inference indicator, demonstrating the ability to provide logical explanations and clearly articulate cause-effect relationships. Those with a pragmatist learning style also lean towards the reasoning indicator, offering straightforward and practical explanations of their chosen strategies. Meanwhile, reflector-type learners display a preference for the inference indicator as well, outlining their steps but expressing uncertainty and hesitation in their answers. In conclusion, students’ critical thinking abilities in numeracy tasks are influenced by their learning styles, with each style showing a different emphasis on specific critical thinking indicators. This research contributes to the field by: (1) providing insights into the relationship between learning styles and critical thinking indicators in the context of numeracy; (2) informing educators on how to tailor instructional strategies to align with students’ learning styles in order to enhance critical thinking; and (3) offering a foundation for future studies aimed at developing numeracy-based learning tools that accommodate diverse learning preferences.